Dynamic right ventricular outflow obstruction: A rare cause of hypotension during anestesia induction. (2017) - Antoniucci, Maria Enrica; Colizzi, Christian; Arlotta, Gabriella; Calabrese, Maria; Corrado, Michele; Guarneri, Sergio; Martinelli, Lorenzo; Scapigliati, Andrea; Zamparelli, Roberto; Cavaliere, Franco
Highlights: Dynamic obstruction of right ventricle outflow tract is a rare hypotension cause. Never described before as cause of hypotension during anesthesia induction. Echocardiography identifies this condition with or without hemodynamic monitoring. Identified dynamic obstruction can be successfully treated with fluid therapy. Abstract: Introduction: Dynamic obstruction of right ventricle outflow tract (RVOTO) is a rare condition that may acutely cause severe heart failure. It has been reported in some hypertrophic cardiomyopathies, after lung transplantation, and in some cases of hemodynamic instability after cardiopulmonary bypass. Presentation of case: We report the case of a 71-year-old man who developed severe hypotension during the induction of general anesthesia for surgical coronary revascularization. Hypotension did not respond to the initial treatment with vasoconstrictors and fluids. RVOTO was suspected during pulmonary artery catheterization because of the difficulty of the catheter tip to move from the right ventricle to the pulmonary artery and, successively, because of the finding of a large gradient between the systolic pressure in the right ventricle and in the pulmonary artery. The diagnosis was confirmed by transesophageal echocardiogram (TEE). Hemodynamics recovered after the infusion of cristalloids, 1 L, and the suspension of vasoconstrictors and inotropes. Discussion: This is the first case in which RVOTO was observed during the induction of general anesthesia. Although this is a rare condition, the diagnostic suspect is of outmost importance because treatment is mainly based on fluid administration, and drugs with positive inotropic properties (like most vasoconstrictors) are contraindicated. Conclusions: RVOTO is an unusual, but possible cause of severe arterial hypotension during general anesthesia induction. TEE is useful for the evaluation of severely hypotensive patients who do not respond to routine treatment with fluids and vasoconstrictors.